Investigation of microemulsion system for topical delivery of Halobetasol propionate (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Halobetasol propionate (HBT) is a topical corticosteroid used to manage Psoriasis. The current studies investigate the microemulsion-based gel of Halobetasol propionate in management of Psoriasis. Based on solubility studies, the oil, surfactant, and co-surfactant determined first. The pseudo-ternary phase diagram was then developed using phase titration method to optimize the surfactant and co-surfactant (Smix) ratio. After determination of concentration range, microemulsion was optimized by simplex lattice design. Independent factors Amount of oil- Capmul MCM C8 (X1), Amount of Smix- Acrysol EL 135: Transcutol HP (X2) and Amount of water (X3) were selected assessed for Globule size, % Transmittance, Zeta potential, PDI and In-vitro diffusion study. Optimized microemulsion containing HBT was converted into gel by using a gelling agent, HPMC K100M to enhance viscosity and maintain the drug's activity by extending residence duration. Optimized HBT-loaded microemulgel evaluated for Spreadability, viscosity, pH, In-vitro diffusion study, Ex-vivo permeation study and Stability study.  Globule size of optimized HBT loaded ME batch was found (119.3±0.58 nm) confirms the micron size of the formulation, %T (98.8±0.02%). The TEM image confirmed the uniform droplet size of the microemulsion and the proper incorporation of drug molecules into the system. The optimized HP loaded ME batch's zeta potential and polydispersity index (PDI) were determined to be -11.2 mV and 0.203, respectively, demonstrating the stability and even distribution of dispersed systems. The finalized formulation of HBT loaded microemulgel showed viscosity value (9862±15.28 cps), Spreadability value (3.58±0.08 gm.cm/sec), pH (5.2±0.08), Drug content was found to be 96.35±0.21%, The ex-vivo permeability of HBT Emulgel within 12 h was 91.92±0.48 % which is 2-fold increase in permeability as compared to HBT marketed gel. Improvement of drug penetration may enhance therapeutic efficacy, reduce dosing frequency, and augment patient compliance in topical medication delivery.